AS1411 aptamer/RGD dual functionalized theranostic chitosan-PLGA nanoparticles for brain cancer treatment and imaging - Chauhan M.; Sonali; Shekhar S.; Yadav B.; Garg V.; Dutt R.; Mehata A.K.; Goswami P.; Koch B.; Muthu M.S.; Singh R.P. (My University, 2025)
Conventional chemotherapy and poor targeted delivery in brain cancer resulting to poor treatment and develop resistance to anticancer drugs. Meanwhile, it is quite challenging to diagnose/detection of brain tumor at early stage of cancer which resulting in severity of the disease. Despite extensive research, effective treatment with real-time imaging still remains completely unavailable, yet. In this study, two brain cancer cell specific moieties i.e., AS1411 aptamer and RGD are decorated on the surface of chitosan-PLGA nanoparticles to improve targeted co-delivery of docetaxel (DTX) and upconversion nanoparticles (UCNP) for effective brain tumor therapy and real-time imaging. The nanoparticles were developed by a slightly modified emulsion/solvent evaporation method. This investigation also translates the successful synthesis of TPGS-chitosan, TPGS-RGD and TPGS-AS1411 aptamer conjugates for making PLGA nanoparticle as a potential tool of the targeted co-delivery of DTX and UCNP to the brain cancer cells. The developed nanoparticles have shown an average particle size <200 nm, spherical in shape, high encapsulation of DTX and UCNP in the core of nanoparticles, and sustained release of DTX up to 72 h in phosphate buffer saline (pH 7.4). AS1411 aptamer and RGD functionalized theranostic chitosan-PLGA nanoparticles containing DTX and UCNP (DUCPN-RGD-AS1411) have achieved greater cellular uptake, 89-fold improved cytotoxicity, enhanced cancer cell arrest even at lower drug conc., improved bioavailability with higher mean residence time of DTX in systemic circulation and brain tissues. Moreover, DUCPN-RGD-AS1411 have greatly facilitated cellular internalization and higher accumulation of UCNP in brain tissues. Additionally, DUCPN-RGD-AS1411 demonstrated a significant suppression in tumor growth in brain-tumor bearing xenograft BALB/c nude mice with no impressive sign of toxicities. DUCPN-RGD-AS1411 has great potential to be utilized as an effective and safe theranostic tool for brain cancer and other life-threatening cancer therapies. © 2024 Elsevier B.V.